STUDENTS’ PERSPECTIVE ON THE DEMAND OF ENGLISH IN FACING ASEAN ECONOMIC COMMUNITY (AEC) - Eka Nurhidayat (Journal of English Language Learning, 2017)
The demand of Asean Community is the use of English, as the language of Asean Community. English become a tool for communicating and connecting with other people around Asean Countries. This paper analyses the result of survey on the student of English Department of Majalengka University. This survey focused on their perspective on the demand of English in facing Asean Economic Community (AEC). The aims of this study are to reveal (1) What should students prepare to face Asean Economic Community (AEC)?; (2) what are students’ perspective on the demand of English in facing AEC?. This study is an investigation of the students’ perspective on the demand of english in facing AEC. This study uses descriptive qualitative method. Meanwhile, the data is collected by using observation, interview, as well as documentation. The descriptive qualitative method covers what should students prepare to face AEC and what students’ perspective on the demand of English in facing AEC.Keywords: The demand of English, students’ perspective, Asean economic Community.